THE ANALYSIS OF ANAPHORA AND ITS THEMATIC ROLES ON A NEWS ITEM - Ayang Winda Sri Widianingsih; Handi Pratama Shadam Hussaeni (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
Nowadays, the issue about muslim population is being discussed and Indonesia is one of the world’s largest Muslim population. At the same time, Indonesia has released film “Rahmat Islam Nusantara” which was written in detail in online media and widely consumed by the public. Based on the excitement, this study focused on the analysis of anaphora to know the reference in every antecedent and continued with thematic roles theory to know the theme of its antecedent on news item to make the news being clear. The study was formulated to answer research questions (1) what does anaphora refer to?. (2) what is thematic roles of that anaphora?. This study employed the qualitative method as research design. The researcher picked archive document analysis research procedure in breaking down the information. “English Syntax : A grammar for English Language Professionals” by Roderick A Jacobs (1995) and “English syntax” by Aarts (2001) were used as the main reference. The analysis showed that there are 31 anaphors found in this article. An anaphora can be found in the same clause with its antecedent whereas thematic roles found is undergoer or theme. Theme role agents create states of affairs, whereas thematic role experiencers have sensory, cognitive, and emotional experiences. Thus, the article demonstrates that what is being said is based on the writer/emotional speaker's experience and his subjective opinion about the problem.